Entre a precisão e espontaneidade: Grotowski e os princípios pragmáticos do trabalho do ator - Alexander Evaristo Araujo de Moraes (2007)
This work approaches the relationship between precision and spontaneity as a pragmatic principle of the actor's craftsmanship base, from the texts and reports of the polish director Jerzy Grotowski. The analysis is led by a pragmatic logic, in which the concepts are dynamically connected with the practice. We observe the pair, precision and spontaneity, situated in one of the main pole of the occidentalactor's performance - the organic pole. We examine the binomial, precision and spontaneity, in the actor's work: in the exercises and in the creative act, according to Grotowski. We evince that the exercises proposed by Grotowski experienced a constant evolution through the years, beginning with strong influences of the eastern classic theater, passing by Stanislavski and arriving in the concept of via negativa. We measure the evolution of the concept of score: as a set of signs to alogical line of impulses and physical actions. The work on physical actions with Grotowski is understood as a development of Stanislavskys work, and it is characterized by a deep research of the flux of living impulses. Finally we understand the effectiveness of the relationship between precision and the spontaneity in the building process of the main character of the spectacle The Constant Prince played by Ryszard Cieslak, one of the most important actors of the group Laboratory Theater.